2023
DOI: 10.3389/fimmu.2023.1191130
|View full text |Cite
|
Sign up to set email alerts
|

Higher systemic immune-inflammation index and systemic inflammation response index levels are associated with stroke prevalence in the asthmatic population: a cross-sectional analysis of the NHANES 1999-2018

Abstract: BackgroundSignificant evidence suggests that asthma might originate from low-grade systemic inflammation. Previous studies have established a positive association between the systemic immune-inflammation index (SII) and the systemic inflammation response index (SIRI) levels and the risk of stroke. However, it remains unclear whether SII, SIRI and the prevalence of stroke are related in individuals with asthma.MethodsThe present cross-sectional study used data from the National Health and Nutrition Examination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 53 publications
(42 reference statements)
1
2
0
Order By: Relevance
“…Similar results were confirmed in some other studies such as esophageal squamous cell carcinoma (27), hepatocellular carcinoma (9). Additionally, SII had been shown to be associated with a wide range of diseases and medical conditions including kidney stones (28), diabetic depression (29), coronary heart disease (30), heart failure (31), asthma (32), rheumatoid arthritis (33), hepatic steatosis (34). For example, Xingpeng et al showed SII was positively associated with a high risk of kidney stones in US adults aged less than 50 (28).…”
Section: Discussionsupporting
confidence: 80%
“…Similar results were confirmed in some other studies such as esophageal squamous cell carcinoma (27), hepatocellular carcinoma (9). Additionally, SII had been shown to be associated with a wide range of diseases and medical conditions including kidney stones (28), diabetic depression (29), coronary heart disease (30), heart failure (31), asthma (32), rheumatoid arthritis (33), hepatic steatosis (34). For example, Xingpeng et al showed SII was positively associated with a high risk of kidney stones in US adults aged less than 50 (28).…”
Section: Discussionsupporting
confidence: 80%
“…Based on previous research, smoking, and drinking status was categorized into three groups: “never,” “former,” and “current” ( 32 , 33 ). Hypertension was defined as systolic blood pressure ≥140 mmHg, diastolic blood pressure ≥ 90 mmHg, self-reported physician diagnosis, or current use of antihypertensive medication ( 34 ).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, recent studies have shown that SIRI was associated with clinical outcomes in patients with stroke. 33,34 Furthermore, previous study showed that SIRI was an independent risk factor for mortality in patients with acute myocardial infarction. 35 In the present study, we found that patients with POD had higher NLR and SIRI before surgery.…”
Section: Discussionmentioning
confidence: 99%